Metabolic Syndrome in Iranian Youths: A Population-Based Study on Junior and High Schools Students in Rural and Urban Areas - Alireza Ahmadi; Mojgan Gharipour; Fatemeh Nouri; Nizal Sarrafzadegan (Journal of Diabetes Research)
Aim. The present population-based study aimed to assess prevalence of metabolic syndrome and itsrelated components in Iranian youth in the different sex, age, and residential subgroups. Method. Overall, 1039 junior high school and 953 high school students were selected using multistage random sampling. Fasting blood sugar, total cholesterol, triglyceride, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels were determined. Trained individuals measured waist circumference and blood pressure. Subjects with MetS were selected according to two definitions provided by the IDF and de Ferranti. Results. Among girls in intervention area, hypertriglyceridemia was more prevalent in rural than in urban areas using IDF definition. Significant differences were observed between boys in rural and urban areas regarding some components of metabolic syndrome including hypertriglyceridemia and high waist circumference. Besides, boys who are residents in urban areas had higher blood pressure, as well as higher waist circumference, than boys in rural areas. Conclusion. Our youth population is at significant risk of developing metabolic syndrome, and the pattern of this phenomenon seems to be discrepant in boys as well as in rural and urban areas probably due to the different lifestyle aspects, genetic factors, and racial differences.